2016
DOI: 10.1002/jsfa.7841
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and evaluation of endophytic Streptomyces endusOsiSh‐2 with potential application for biocontrol of rice blast disease

Abstract: Endophytic S. endus OsiSh-2 has potential as a biocontrol agent against rice blast in agriculture. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 50 publications
0
42
0
Order By: Relevance
“…This finding revealed that although chitinolytic activity of Streptomyces and digestion of the fungal cell wall is an effective mechanism of growth inhibition (Gherbawy et al, 2012), other mechanisms such as antibiosis and even an enzyme like protease (Xu et al, 2016) that is less studied are also involved in antagonism. Interestingly, there was a significant correlation between IAA and siderophore productions and FOL growth inhibition, showing relationship between PGP features and antagonistic activities in Streptomyces .…”
Section: Discussionmentioning
confidence: 99%
“…This finding revealed that although chitinolytic activity of Streptomyces and digestion of the fungal cell wall is an effective mechanism of growth inhibition (Gherbawy et al, 2012), other mechanisms such as antibiosis and even an enzyme like protease (Xu et al, 2016) that is less studied are also involved in antagonism. Interestingly, there was a significant correlation between IAA and siderophore productions and FOL growth inhibition, showing relationship between PGP features and antagonistic activities in Streptomyces .…”
Section: Discussionmentioning
confidence: 99%
“…But, we find that the preventive effect is better than the therapeutic effect. To our knowledge, the present chemical fungicides are only effective for preventing and not effective for curing rice blast [ 22 ]. The result obtained with GYLH001 shows a similar pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Last, the mixture was poured into Petri plates. The fungus cake of Guy11 were transferred to center of medium and incubated at 28°C in the incubator [ 22 ]. The M .…”
Section: Methodsmentioning
confidence: 99%
“…S1). The inhibition percentage was calculated as described in the literature 26 …”
Section: Methodsmentioning
confidence: 99%